Tick species composition and associated haemoparasites of cattle in a semi-arid area of Karamoja, Uganda - Stoltsz, Wilhelm Heinrich (University of Pretoria, 2020)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2019.